Comparison of the training load of professional athletes between modes of volleyball specific drills and strength conditioning - de Faria, B. S. H.; Costa Campos, Y. D. A.; Toledo, H.; Miranda, R.; Vianna, J. M.; Bara Filho, M. G. (Journal of Physical Education, 2020)
The aim of this study was to compare the training load in three types of training of a professional volleyball team. Participants were 28 players (26.6 ± 4.7 years, 91.5 ± 8.5 kg; 194.1 ± 6.0 cm). A descriptive analysis of 29 technical training sessions, 84 technical-tactical training sessions and 75 training sessions, and of the variables that compose the training load, PSE and the duration of the session were performed, and were then collected on average and standard deviation according to with type of training. To analyze the data, the Shapiro-Wilk test was adopted, and then the Anova Two-Way test was applied with Tamhane's Post Hoc and the effect size was also used for analysis of the comparisons. The results demonstrated significant responses and a large effect size when compared to technical and tactical-to- strength training (T = 1.2: large; p = 0.002); TTxM (TE = 1.3: large, p = 0.001) and the duration of the session / external load in the TxM training (TE = 1.7: large; p = 0.001); TTxM (TE = 2.0: large, p = 0.001), whereas the PSE of the session showed only a sigifcant difference TTxM (TE = 0.8: moderate; p = 0.001). The stimuli of specific training of court as technician and technician-tactician promoted greater internal load in the athletes than the strength training, mainly through the influence of the variable time of the session that reflected to external load.